Impact analysis of the Malaysia’s economy on the palm oil stock returns in Malaysia, Singapore, and Indonesia through NARDL model - Tok, Hui Mei (2023)
In this study, we investigate the impact of Malaysia economic conditions on the palm oil stock returns in Malaysia, Indonesia, and Singapore. As one of the top producers and traders of palm oil globally, changes in the palm oil industry affect the economies of all three countries. In 2022, the Russia-Ukraine conflict has triggered a profit surge in the Malaysian palm oil industry. As such, we employ the Non-Linear Autoregressive Distributed Lag (NARDL) framework to examine the asymmetric influence of the Malaysian economic condition on palm oil stock returns in Malaysia, Indonesia, and Singapore. Our results indicate that in the long run, the exchange rate, inflation rate, and crude oil price significantly determine palm oil stock returns. Positive and negative shocks of in the exchange rate show a significant positive relationship with the palm oil stock return, while only positive shocks in the inflation rate and crude oil price significantly affect palm oil stock return fluctuations. Overall, our study sheds light on the interdependence of the palm oil industry and macroeconomic factors, giving insights for investors and policymakers in the palm oil industry.